New species of Desmiphorini (Coleoptera, Cerambycidae, Lamiinae) from Costa Rica and Ecuador - Martins, Ubirajara R.; Galileo, Maria Helena M. (Papéis Avulsos de Zoologia, 2009)
New species are described: Eupogonius lateralis sp. nov., Estola nigrodorsalis sp. nov. and Pseudestoloides rubiginosa sp. nov. from Heredia (Costa Rica); Pseudestoloides affinis sp. nov. from Guanacaste and Puntarenas (Costa Rica); Mimopogonius hovorei sp. nov. from Azuay (Ecuador).